Reevaluation of presentation and course of idiopathic intracranial hypertension – a large cohort comprehensive study. (31st December 2012) - Pollak, L.; Zohar, E.; Glovinsky, Y.; Huna‐Baron, R.
<x xml:space="preserve">Abstract</x> Objectives We analyzed the clinical and ophthalmological findings in a large group of patients with idiopathic intracranial hypertension (IIH) trying to find factors that might influence the course of the disease. Materials and methods Medical records of patients with IIH were retrospectively reviewed. The patients included were women after menarche and men older than 18 years of age who were followed up for at least 1 year. Results Eighty‐two patients (89% women) with a mean age of 30.2 ± 12.0 years were included. The prevailing complaint was headache and transient visual obscurations followed by tinnitus and double vision. Eighty‐two percent of patients were overweight at the time of diagnosis. Overweight patients had higher opening cerebrospinal fluid (CSF) pressure than patients with normal weight did. The grade of papilledema correlated with the CSF opening pressure. Inverse correlation was found between the depression of the visual field sensitivity and the grade of papilledema. The mean follow‐up time was 61.3 ± 62.3 months. Eighty‐four percent of the patients have improved while in 22% CSF diversion procedures or optic nerve decompression was required. The mean body mass index (BMI) at the end of follow‐up decreased significantly. Sixty‐seven percent of the patients suffered a recurrence of IIH. The number of recurrences inversely correlated with weight loss. Visual field defects on presentation were encountered more frequently in patients with recurrence. Women with recurrence had a history of more pregnancies. Conclusions Our results confirm the strong association between overweight and IIH. The recurrence rate seemed to be influenced by the obstetrical history and the severity of visual field defects at presentation. In contrast to some previous studies, we have found an interrelation between the CSF opening pressure, grade of papilledema and depression of the visual field sensitivity.